Numerical modeling to study the effect of small bottom irregularities on steady flow in homogeneous ocean (2018)
The numerical modeling of topographic waves is based on the continuity and momentum equations. The solutions of these equations for the vertical and horizontal velocities and surface elevation of the oceans were obtained through a FORTRAN- program that was run using different values of bottom slope (a), coefficient of bottom friction (r) at different intervals (n). Slopes of the plots of horizontal, vertical velocities and surface elevation of the ocean for flat bottom ocean and fixed values of bottom friction were obtained. Similarly, slopes of the plots of resultant velocity against surface elevation and surface elevation versus horizontal and vertical velocity were also obtained. The resultant velocity (c) against the surface elevation η of the ocean produced negative slopes. The low value of slopes is an indication that the ocean waves move slowly and steadily.